The Influence of Marketing Mix on Loyalty of Internal Medicine Outpatients at the RSIA Hospital in Aceh Province - Masyudi; Riski Muhammad; Aris Winandar; Yuliani Safmila; Namira Yusuf (Universitas Serambi Mekkah, 2024)
Patient loyalty cannot be separated from the strategy used by the hospital. Selection of strategy in a hospital is a major concern that must be prioritized. One strategy that believed able to increase patient loyalty is a marketing mix. It is known to RSIA that RSIA Aceh Province has implemented a product mix such as the Iva test and is equipped with adequate tools, but there are still service products that are not yet supported by adequate tools.enough until caused the RSIA management to have to refer the patient back to RSUDZA. This research aims to determine the influence of the marketing mix (product, place, promotion, human resources, physical appearance, service process, and price) on the loyalty of Internal Medicine Outpatient Polyclinic patients at the Aceh Province Women's and Children's Hospital in 2023. This research method This is a quantitative research with a cross sectional design. The population of this study were outpatients from the internal medicine clinic of RSIA Aceh Province. The sample used in this study used the Lemeshow equation to obtain a sample of 96 people. Data analysis was carried out univariate, bivariate and multivariate. The research results show that there is an influence of product dimensions (p=0.008), place (p=0.003), promotion (p=0.041), human resources (health workers) (people) (p= 0.000), the physical appearance of the place of service (p=0.024) and the service process (process) on patient loyalty at RSIA Aceh Province (p=0.000). The most dominant factor influencing patient loyalty at RSIA Aceh Province is the service process, as evidenced by the Adjusted Odd Ratio (AOR) value of 8.492 (p=0.021≤0.05). It is hoped that the management of RSIA Aceh Province can improve physical and promotional factors which are believed to have an impact on patient loyalty.